2013
DOI: 10.32832/tadibuna.v2i2.562
|View full text |Cite
|
Sign up to set email alerts
|

Pemikiran Pendidikan Ki Hadjar Dewantara dalam Perspektif Pendidikan Islam

Abstract: <p>Education is the guidance in the growth of children's lives so that they can achieve salvation and happiness. Education must have a vision and a noble mission; the vision is far into the future beyond time and space, while the mission of Islamic education is on accordance to the concept of Tawheed, so that it will always relevant in every time and all conditions. Education should be based on divine revelation (al-Qur'an and al-Hadith). If education is not guided and does not display the spirit of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 0 publications
0
5
0
5
Order By: Relevance
“…A number of articles have concluded that the concept of Education in the context of Ki Hajar Dewantara is relevant to Islamic Religious Education [15], and Ki Hadjar's multicultural education was nationalistic and universal in nature [16]. One of the main purposes [17] of the educational institution is to enable a person/student to become active, independent and responsible, to promote the personal skills and competences (including knowledge, skills and values) of a student, enabling them to shape their own and the community's life independently, critically.…”
Section: Resultsmentioning
confidence: 99%
“…A number of articles have concluded that the concept of Education in the context of Ki Hajar Dewantara is relevant to Islamic Religious Education [15], and Ki Hadjar's multicultural education was nationalistic and universal in nature [16]. One of the main purposes [17] of the educational institution is to enable a person/student to become active, independent and responsible, to promote the personal skills and competences (including knowledge, skills and values) of a student, enabling them to shape their own and the community's life independently, critically.…”
Section: Resultsmentioning
confidence: 99%
“…Akan tetapi pengajaran budi pekerti mengandung maknapentransfer materi tentang kehidupan jiwa atau perikeadaban manusia. Atau dengan kata lain, kaharusan memberi keterangan dan penjelasan mengenai budi pekerti secara lebih luas (Muthoifin & Jinan, 2015).…”
Section: Karya Tulis Ki Hajar Dewantaraunclassified
“…Didirikan pada tahun 1954, TK Taman Indria menjadi salah satu TK yang telah berumur lebih dari setengah abad. TK Taman Indria merupakan salah satu bagian dari sebuah perguruan yang memiliki filosofi dan karakteristik yang mencerminkan filosofi Ki Hadjar Dewantara, salah satu tokoh pendidikan yang merupakan Bapak Pendidikan Nasional Indonesia Pendidikan karakter merupakan jiwa dalam pendidikan, demikian ungkapan dari Ki Hadjar Dewantara (Muthoifin & Jinan, 2015). Sebagai sebuah lembaga yang berada di bawah naungan Perguruan Tamansiswa, pendidikan karakter di TK Taman Indria memiliki karakteristik atau ciri khas yang berbeda dengan yang diterapkan di tempat lain.…”
Section: Hasilunclassified
“…Apriliyanti, Hanurawan, Sobri, Sistem Among dalam… 1052 PEMBAHASAN Pendidikan karakter menurut Ki Hadjar Dewantara dinamakan sebagai pendidikan budi pekerti (Dewantara, 2013;Tamansiswa, 2013) yang diartikan sebagai bulatnya jiwa manusia, sebagai jiwa yang" berasas hukum kebatinan". Pendidikan karakter merupakan jiwa dari pendidikan menurut Ki Hadjar Dewantara (Muthoifin & Jinan, 2015). Hal tersebut menunjukkan bahwa pendidikan karakter menjadi suatu prioritas dalam suatu lembaga yang berada di bawah naungan Perguruan Tamansiswa.…”
Section: Strategi Dalam Melestarikan Nilai-nilai Luhur Pendidikan Karakter Ki Hadjar Dewantara DI Tk Taman Indriaunclassified